Kcnv2 E151X Mouse Captures Hallmarks of KCNV2 ‐Associated Retinal Dystrophy - Nermina Xhaferri; Sumit Biswas; Benjamin Davies; Moritz Lindner (Clinical & Experimental Ophthalmology, 2026)
ABSTRACT Background KCNV2‐associated retinopathy is a rare inherited retinal dystrophy caused by variants in the KCNV2 gene, leading to disrupted photoreceptor behaviour and progressive deterioration of vision. Patients have characteristic electroretinography abnormalities, including reduced cone response, delayed and reduced rod response to low light flashes and paradoxically large rod‐driven response to bright flashes of light. To model this condition, we have generated a Kcnv2 E151X mouse line and assessed its structural and functional retinal features. Methods We have employed CRISPR/Cas 9 gene editing technology to generate a mouse line with an early stop mutation in position E151—orthologous to the commonly encountered E143X mutation in humans—and performed a combination of immunohistochemistry and Western blot to confirm the absence of the full‐length KCNV2—encoded protein, Kv8.2. Next, to assess how closely it models the human disease, we have characterised the KCNV2 mutant mouse line at histological and functional levels, via immunohistochemistry and electroretinography experiments, respectively. Results Kcnv2 mutant mice showed markedly reduced photopic responses and reproduced the supernormal rod phenotype described in affected individuals. In the morphological context, mutant retinas demonstrated strong glial fibrillary acidic protein upregulation together with reduced cone arrestin positive cell counts and photoreceptor layers, indicating photoreceptor loss. Conclusions The Kcnv2 mutant mouse line replicates key functional and structural hallmarks of KCNV2‐associated retinopathy. This model provides a relevant platform for mechanistic studies and preclinical evaluation of gene‐based or pharmacological therapies targeting cone and rod photoreceptor dysfunction.